Chicken egg white: Hatching of a new old biomaterial. (November 2020) - Jalili-Firoozinezhad, Sasan; Filippi, Miriam; Mohabatpour, Fatemeh; Letourneur, Didier; Scherberich, Arnaud
Graphical abstract: Abstract : Chicken egg white is an abundant, inexpensive and natural source of important proteins such as ovalbumin and lysozyme. Thanks to its bioactivity, easy handling, anti-bacterial activity and biodegradability, egg white is being used since centuries as excipient of poultices for the treatment of various disorders. Owing to unique thermal and electrical features, egg white is currently used in bioplastic development and in fabrication of field-effect transistors, but it could also contribute to various biomedical applications in the future. Indeed, egg white and some of its byproducts were shown to improve tissue engraftment and to stimulate angiogenesis, making it particularly attractive in wound healing and tissue engineering applications. Moreover, egg white can be manipulated to obtain versatile platforms for tridimensional in vitro tissue models or drug delivery systems. This review describes the structure and physicochemical properties of egg white as well as its biological features. It also summarizes fabrication methods from egg white for the generation of functional platforms, and provides a comprehensive overview of the role and performance of egg white in various biomedical applications. Finally, new perspectives for future studies in health with this ancient material are critically discussed.